PENGARUH PENDIDIKAN ANAK USIA DINI TERHADAP PERKEMBANGAN KONDISI SOSIAL-EMOSI ANAK USIA PRASEKOLAH - Asmarita, Asmarita; Hamid, Abdurrahman; Utami, Agnita (Universitas Ahmad Dahlan, 2020)
The social and emotional development of young children is affected by many stimulating factors, and one of those factors is early childhood education. However, not all pre-school children have the opportunity to attend early childhood education. This study was aimed at comparing children’s social and emotional development of those who attend and do not attend early childhood education. This comparative study was carried out using a cross-sectional approach among 72 participants divided into 2 groups: 36 participants who attend early childhood education and 36 participants who do not attend early childhood education. Accidental sampling technique was applied to select samples, Non-parametric statistical test employed was the Mann Whitney test. Comparison value of children attending and not attending early childhood education was P-value 0.000; the emotional comparison value was P-value 0.040. It means there were differences in social and emotional development between children who attend early childhood education and those who do not attend early childhood education. It can be concluded that early childhood education can help stimulate the development of children. Parents should pay more attention to their children’s social and emotional development, whereas if parents cannot be the medium to support children’s social and emotional development, they should engage their children to early childhood education.